Group development and group leadership in student affairs - Killam, Wendy K.; Carter, Adam, 1980-; Degges-White, Suzanne (Lanham, rowman & Littlefield, 2021)
"The purpose of this book is to provide readers with an overview of basic group dynamics and techniques that are effective in Higher Education and Student Affairs settings"--
Introduction to groups and basic group dynamics / Susan J. Foster, Rodney E. Harris, and Denita Hudson -- Overview of common group theories / Emily Donald and Adam Carter -- Group leadership techniques / Marty Jencius -- Culturally responsive group leadership / Christian Chan, Tamekia Bell, and Tahani Dari -- Leading a team / Mary Mayorga -- Being an effective group member / Adam Carter and Emily Donald -- Team and committee work / Suzanne Degges-White and Wendy Killam -- Being an advisor for student groups / Kimberlee Ratliff -- Creating group opportunities for students / Siu-Man Raymond Ting and Mona Nour -- Residence life and the integration of groups / Shannon Dean-Scott and Peter Theodore Ingwersen -- Group opportunities for first generation students / Angelica Tello -- Groups to support academically vulnerable students / Rebekah Reysen -- Groups for student veterans / Wendy Killam and Suzanne Degges-White -- Groups to support survivors of sexual assault / Eve Kagan and Katherine M. Atkins -- Groups for students with high functioning autism and Asperger's / Wendy Killam -- Groups for single mothers / Emily Donald and Adam Carter -- Technology and groups in student affairs practice / Emily Donald and Adam Carter -- Current issues and future trends / Jane Webber, J. Barry Mascari, Robert Kitzinger, and Stephanie Bobbit.
Includes bibliographical references and index.
Keywords: Counseling in higher education -- United States; Group counseling -- United States; Group guidance in education -- United States; Student affairs services -- United States